Beauty Unrealized : spider webs of personal universes seeking a form - Van Weyenberg, Astrid; Public Space With A Roof, Amsterdam (Amsterdam : Public Space With A Roof Amsterdam Roma Publications Amsterdam, 2007)
Hirschhorn, Thomas ; Cytter, Keren ; Garnett, Robert ; Michaud, Philippe-Alain ; Goupy, Benoît ; De Broin, Michel ; Fennis, Maurits ; Pisano, Falke ; Geers, Kersten ; Gandolfi, Fiora ; Avikainen, Adam ; Sullivan, Catherine ; Bernardelli, Francesco ; Pasaiko, Oksana ; Nagtzaam, Marc ; Manders, Mark ; Baroni, Claudio ; Marcaccio, Fabian ; Dewey, John
Engels
Published on the occasion of the exhibition "Beauty unrealized : spider webs of personal universes seeking a form" at Public Space With A Roof in Amsterdam, 14.12.2006 - 08.04.2007
boek